(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the concept of Artificial Intelligence (AI)-based fiqh muamalah learning in Islamic Religious Education (IRE) at Madrasah Aliyah. The study employed a Systematic Literature Review (SLR) method with a qualitative approach. Data were collected from various relevant scientific articles, journals, conference proceedings, and books retrieved through Google Scholar, Scopus, and Crossref databases. Data analysis was conducted using the content analysis technique to identify concepts, opportunities, challenges, and development strategies for AI-based fiqh muamalah learning. The findings indicate that the utilization of AI can enhance the effectiveness, interactivity, flexibility, and personalization of learning. Technologies such as ChatGPT, Islamic law consultation chatbots, adaptive learning systems, AI-based assessments, and digital sharia transaction simulations can assist students in understanding muamalah concepts in a more practical and contextual manner. However, the implementation of AI in fiqh muamalah learning still faces several challenges, including teachers’ digital competence, technological infrastructure limitations, digital ethics issues, and the validity of Islamic information generated by AI. The limitation of this study lies in its reliance on secondary data sources, which do not fully reflect the direct implementation of AI in Madrasah Aliyah. Future studies are recommended to conduct field research to examine the effectiveness of AI-based fiqh muamalah learning models in educational practice.